Tackling the Last Hurdles of Poverty Entrenchment: An Investigation of Poverty Dynamics for Ghana during 2005/06–2016/17 - Hai-Anh Dang; Dhushyanth Raju; Tomomi Tanaka; Kseniya Abanokova (Institute of Labor Economics (IZA), 2024)
Ghana has managed to consistently keep its poverty rate lower than the regional average over the past 25 years, but this positive trend slowed down recently. We investigate the dynamics of overall, moderate, and extreme poverty in Ghana during 2005/06–2016/17, addressing the lack of actual panel data by constructing synthetic panel data from repeated cross-sectional data. While we find considerable conditional chronic (extreme) poverty rates hovering around 50-60 percent, there is more upward mobility than downward mobility. Poor households are also more likely to have enjoyed stronger consumption expenditure growth. Our findings suggest that factors such as education attainment, female household headship, urban residence, and non-agricultural work are positively correlated with poverty reduction. Compared to all other correlates, education attainment appears to be most effective in pushing households out of poverty and keeping them from falling into poverty.
Keywords: C15; D31; I31; O10; O57; 330; poverty; poverty dynamics; pro-poor growth; synthetic panel; household surveys; Ghana; sub-Saharan Africa